Rate of stripe rust (Puccinia striiformis) on wheat in the highland and lowland area - Ashagre Asnakew Zewde; Jhon Hardy Purba (Journal of Agriculture and Applied Biology, 2022)
Stripe (Yellow) rust caused by Puccinia striiformis f.sp. tritici (Pst) is a crucial wheat disease causing severe damage to cultivated susceptible wheat varieties. The wheat yellow rust assessment was conducted during the primary rainy season of 2018/19 at Ada’a, Lume, and Gimbichu using the zigzag disease assessment method. Disease data, agro-ecological data, and other essential parameters were recorded. The disease was prevalent in all districts by diverse incidence and severity ranges. This implies that yellow rust is distributed wheat disease at all surveyed potential districts. The highest yellow rust prevalence, 62.5% was recorded at Gimbichu district; conversely, the lowest prevalence 31.25% was recorded at Ada’a district. The highest severity and incidence of yellow rust 60% and 100%, respectively, was recorded at Ada’a district with susceptible reaction. In comparison, the lowest severity and incidence (30% and 5%) respectively were recorded at Lume districts with moderately sensitive responses. Many distributions and occurrences govern yellow rust. The highest incidence of yellow rust, namely 100% on land cultivated with kakaba and kubsa wheat bread varieties, occurred at the milk growth stage to the ripe stage. The local cultivar has shown the lowest incidence and severity percentage with moderately susceptible responses than improved varieties.